Comparing technology and regulatory landscape of probiotics as food, dietary supplements and live biotherapeutics - Spacova, Irina; Binda, Sylvie; ter Haar, Jessica Anne; Henoud, Solange; Legrain-Raspaud, Sophie; Dekker, James; Espadaler-Mazo, Jordi; Langella, Philippe; Martín, Rebeca; Pane, Marco; Ouwehand, Arthur C. (Frontiers in Microbiology, 2023)
Application of beneficial microorganisms as probiotics targets a broad range of intended uses, from maintaining health and supporting normal bodily functions to curing and preventing diseases. Currently, three main regulatory fields of probiotic products can be defined depending on their intended use: the more similar probiotic foods and probiotic dietary supplements, and live biotherapeutic products. However, it is not always straightforward to classify a probiotic product into one of these categories. The regulatory nuances of developing, manufacturing, investigating and applying each category of probiotic products are not universal, and not always apparent to those unfamiliar with the various global probiotic regulatory guidelines. Various global markets can be significantly different regarding legislation, possible claims, market value and quality requirements for the development and commercialization of probiotic products. Furthermore, different probiotic product categories are also linked with variable costs at different stages of product development. This review outlines the current landscape comparing probiotic foods, probiotic dietary supplements, and live biotherapeutics as probiotic products from a regulatory lens, focusing on product development, manufacturing and production, and clinical research agenda. The aim is to inform and promote a better understanding among stakeholders by outlining the expectations and performance for each probiotic product category, depending on their intended use and targeted geographical region.